DAMPAK PROGRESSIVE WEB APPLICATION (PWA) TERHADAP PENINGKATAN ENGAGEMENT DAN DWELL TIME PADA APLIKASI E-COMMERCE - Dwi Purnomo Putro; Joko Suprianto; Puput Eka Suryani (IDEALIS : InDonEsiA journaL Information System, 2025)
The advancement of digital technology encourages businesses to adopt e-commerce applications. However, the successful implementation of e-commerce applications still faces challenges in improving key indicators such as user engagement and dwell time. Progressive Web App (PWA) offers a technological solution with fast performance, high stability, and easy access across various devices, which is expected to address these challenges in e-commerce. While many e-commerce applications are available, not all of them have adopted PWA. Although PWA has the potential to address these challenges, its impact on engagement and dwell time has not been widely studied, particularly using a quantitative approach based on web analytics data. Previous research on PWA has largely focused on technical aspects and general user experience surveys. This study aims to measure the impact of PWA on user engagement and dwell time in e-commerce applications. It employs a quantitative method with a quasi-experimental approach, involving 50 participants divided into an experimental group (using PWA) and a control group (without PWA). Data were collected through Google Analytics and analyzed using the Shapiro-Wilk normality test and parametric analysis. The results show that PWA significantly increases engagement and dwell time, with pageviews rising by 48.79%, session duration increasing by 67.26%, and dwell time growing by 55.56%. These findings demonstrate that PWA not only enhances application efficiency but also improves user experience. This study contributes to the e-commerce literature and recommends the adoption of PWA to optimize user interaction and support sustainable business growth.